A importância da descrição em O Guarani (1857), de José de Alencar - Viana, Juliane Bezerra Seraphim [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This paper aims at studying the description functioning in O Guarani (1857), José de Alencar´s masterpiece (1829-1877), as a main resource for the narrative development. In order to achieve that, descriptive statements about spaces and main characters of the plot were chosen as well as the stylistic traits, based on theoretical assumptions in both Gerárd Genette ´s Frontiers of Narrative (1973) and Philippe Hamon ´s What is a description? (1976), were analyzed. In the analysis of the space description, it is realized that Alencar, through his narrator, sets up fundamental scenarios of the work that not only predict but also explain past or future actions, besides helping define the subjects´ character. The description of the characters make up images that highlight their physical and psychological features, as well as their gestures and costumes, which is considered decisive for composing each character´s point of view, making it individualized. The stylistic traits used for these descriptions generally follow a pattern. This paper therefore discusses the functionality of the novel plot description, which is used for observing the descriptive expedients both as O Guarani´s reading guides and global understanding, based on the narrative description use

A presente dissertação tem por objetivo estudar o funcionamento da descrição em O Guarani (1857), de José de Alencar (1829-1877), enquanto recurso decisivo para o desenvolvimento da narrativa. Para cumprir tal objetivo, selecionam-se enunciados descritivos sobre espaços e personagens principais da trama, bem como analisam-se traços estilísticos, com base nos pressupostos teóricos sobre descrição de Gerárd Genette, em Fronteiras da narrativa (1973) e de Philippe Hamon, em O que é uma descrição? (1976). Na análise da descrição dos espaços, aponta-se que Alencar, por meio de seu narrador, fixa cenários fundamentais da obra, que prenunciam e explicam ações ocorridas ou vindouras, além de auxiliar na definição do caráter dos indivíduos. A descrição das personagens compõe imagens que evidenciam seu aspecto físico e psicológico, além de gestos e trajes, decisivos para a composição do ponto de vista de cada personagem, particularizando-a. Os traços estilísticos utilizados nessas descrições seguem, geralmente, um padrão. Esta dissertação, portanto, discute a funcionalidade da descrição no enredo do romance analisado para, com base em estudos sobre o uso da descrição na narrativa, observar os expedientes descritivos como orientadores de leitura e facilitadores da compreensão global de O Guarani
Keywords: Alencar, José de 1829-1877; Literatura brasileira - História e crítica; Literature